2021
DOI: 10.46542/pe.2021.211.6572
|View full text |Cite
|
Sign up to set email alerts
|

Choice of pharmacy, professional perceptions, and career plans of students in three Nigerian schools of pharmacy

Abstract: Background: A progressive increase in the number of students admitted to study pharmacy in Nigeria has not been met with sufficient documented evidence of their preferences and motivations. Studies on this would aid in designing a programme that matches student expectations, whilst maintaining regulatory requirements. Aim: This study evaluated students’ preferences in wanting to study pharmacy, perceptions of the profession and career choice. Method: A cross-sectional questionnaire-based study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
3
4
1
Order By: Relevance
“…Despite their positive attitudes however, findings from our study and others (Beedemariam et al, 2014;James et al, 2018;Isah et al, 2021;Sajjad et al, 2021) have also highlighted that many pharmacy students would not be willing to study pharmacy a second time.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Despite their positive attitudes however, findings from our study and others (Beedemariam et al, 2014;James et al, 2018;Isah et al, 2021;Sajjad et al, 2021) have also highlighted that many pharmacy students would not be willing to study pharmacy a second time.…”
Section: Discussioncontrasting
confidence: 66%
“…Attitudes and perceptions of pharmacy students towards the profession have generally been reported to be positive. Just as in this study, several other studies (Beedemariam et al, 2014;James et al, 2018;Isah et al, 2021;Sajjad et al, 2021) all reported that majority of their respondents wanted a career in pharmacy, were proud to tell others that they were pharmacy students and were committed to the values of the profession. Similarly, although only one study (that we are aware of) has specifically assessed pharmacy students' satisfaction with their decision to study pharmacy (Shen et al, 2014), the investigators also reported that most of their respondents were satisfied.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations